Spirituality and lifestyle in Human Medicine students of Universidad Peruana Unión, Lima 2017 - Alva Rosnay, Lea Rosmery (2019)
Objective: To determine the relationship between spirituality and lifestyle in students of HumanMedicine. Materials and methods: Quantitative approach, non-experimental design, correlation typeand cross-sectional type. The selection of the sample was made by non-probabilistic sampling forconvenience and was made up of 176 students. The questionnaire used for data collection was the“spirituality questionnaire” created by Parsian and Dunning (2009) and translated and adapted intoSpanish by Diaz (2012). In turn, to measure the lifestyle variable, it was used the “SN - 52” questionnaire,created by Walker, Sechrist, and Pender (1996). It should be noted that both instruments presented ahigh Cronbach Alpha coefficient with a value of 0.9, demonstrating their reliability. Results: There wasa relationship between spirituality and the lifestyle with a p-value of 0.002, according to the Chi-squarestatistical test. Similarly, a relationship was found between the dimensions of spirituality and lifestylewith a p-value <0.05. Conclusion: There is a relationship between the study variables.